Stock Liquidity and Company Annual Reports. How Does Publishing the Annual Report Affect Stock Liquidity? - Zeinali, Tohid; Fryczak, Jan Makary (Nauki o Finansach, 2025)
Aim: This study examines how management reports affect stock liquidity and compares the responses of stocks with low, medium, and high liquidity. Methodology: Stocks were classified into three liquidity groups based on the median Amihud (ILLIQ) ratio. The Wilcoxon test and the Mann-Whitney U test were used to verify the result. Lastly, quantile regression was used to show the role of initial liquidity levels, especially in higher quantiles. Findings: The main findings show that management reports generally affect stock liquidity, but stocks with lower liquidity display a stronger reaction. This means that new disclosures, especially for companies that already have weaker liquidity, can create larger market fluctuations. Implications: These results are significant for investors and market regulators because they can use the insights to better manage risk and make more informed decisions. From a managerial perspective, understanding how liquidity responds to disclosures can help companies refine their communication strategies. Researchers can also apply this event-based approach to study how other types of reports or market conditions influence liquidity. Originality/value: Focusing on management reports and their impact on liquidity in a less-studied market and using both nonparametric tests and quantile regression make this research unique, helping to understand how stocks with low liquidity may show more changes after management disclosures.
Financial Sciences. Nauki o Finansach, 2025, vol. 30, no. 2, s. 1-13
Keywords: management reports; stock liquidity; event-based method; Wilcoxon tests; quantile regression